The Role of Bhabinkamtibmas through the "Duren Trawas" Program to Prevent Fraud Crimes at Mojosari Police (Indonesian Journal of Police Studies, 2024)
One of the disturbances in social security and social security in the Mojosari sub-district under the jurisdiction of the Mojosari Police is fraud. This is proven by the high number of fraud cases. Police efforts are needed to maintain security and social order, one of which is by conducting outreach through the Duren Trawas program. This research aims to describe the role and factors that influence the implementation of the role to prevent criminal acts of fraud. The theories used in this research are communication theory, management, community participation, and SWOT analysis. The concepts used are the concept of role, Bhabinkamtibmas, activity objectives, the role of Bhabinkamtibmas, the Duren Trawas program, and fraud. The results of this research show that the role of Bhabinkamtibmas through the Duren Trawas program to prevent criminal acts of fraud at the Mojosari Police has overall been going well. This can be seen from the role of Bhabinkamtibmas members in Article 1 Paragraph 4 of the Regulation of the Head of the National Police of the Republic of Indonesia Number 7 of 2021, namely as positive dynamiters, motivators and facilitators, as protectors, protectors, and servants of the community to create a sense of security and peace in the community. sub-district, as well as a community guide for the realization of legal and social security awareness and increasing community participation. The inhibiting factor is the lack of awareness in some communities, so regular visits are needed in sub-districts before implementing the Duren Trawas program so that the community plays a more active role in participating in outreach activities and the public should increase insight by leveraging the latest media literacy to prevent crime.
Keywords: Peran, Bhabinkamtibmas, Program Duren Trawas, Penipuan.